Influência de diferentes anticongelantes para a água gelada produzida por um chiller de absorção de LiBr em uma usina termoelétrica na absorção de gases. - Gamboa, Hugo Geovanni Gomes (2017)
A lower specific fuel consumption has been the main reason for conducting research and technological developments in thermal production area of energy. One of the options to reach that desired condition is an efficient control of the engine block temperature in the generator group of a thermal plant. To this, they were tested different antifreeze, which gave the deionized water in preparation for the secondary refrigerant, reductions in thermos physical properties of their specific heat and thermal conductivity. After choosing the antifreeze with the help of experimental design using central composite rotate design (CCRD), the 30 % ethylene glycol solution had their performance compared to deionized water on a bench scale unit of a diesel generator group. Experimental data on the response of aqueous solution of ethylene glycol, against temperature variations at the entrance of the generator motor unit were monitored and stored in an electronic register (FieldLogger) and subsequently analyzed graphically with the aid of a computer. Although a lower value for the specific heat of the aqueous ethylene glycol solution had, as expected, produced pulses faster response to temperature changes in the engine block input, from the 70 ° C reduction in thermal conductivity contributed to production of pulses lower for pure deionized water. However, in the power range tested the aqueous solution of ethylene glycol presented as advantages a reduction of specific fuel consumption of the order of 42% between 68 °C and 75 °C.